The Panorama of Publications on Geoturism in Brazil from bibliometric analysis - Rodrigues, Suzana de Mendonça; Mello Affonso , Gustavo Uchôa de; Nascimento, Marcos Antonio Leite do (Revista Brasileira de Ecoturismo (RBEcotur), 2022)
This article aims to present the distribution of scientific publications on Geotourism, carried out in Brazil, from 2010 to 2019. For this, a census was carried out based on the platforms Elsevier, Google Scholar, Plataforma-Capes, Scielo, Oasis, and Speel, which allowed us to identify the published works and to filter them according to the parameters: (a) being published in journals; (b) having the term geotourism, geotouristic (masculine noun) or geotouristic (feminine noun) in the title; (c) being within the stipulated period; and (d) being in any language, as long as it has been published in Brazil. Along with the survey, bibliographical research was carried out to support the interpretations and discussions. The results focused on five groups involving year, language, study location, publication, and authors. The main results show that there was an increase in the number of articles in that decade; Minas Gerais is the state with more articles; UFRJ's Anuário de Geociências (Geosciences Yearbook) is the journal that publishes the most on the topic; there is a greater number of articles produced in pairs; the Federal University of Uberlândia has the most significant number of publications; the ten main authors who publish about Geotourism in Brazil were identified.